Synthesis and characterization of low-molecular-weight π-conjugated polymers covered by persilylated β-cyclodextrin - Farcas, Aurica; Resmerita, Ana-Maria; Stefanache, Andreea; Balan, Mihaela; Harabagiu, Valeria (Beilstein Journal of Organic Chemistry, 2012)
The paper reports the preparation of a poly[2,7-(9,9-dioctylfluorene)-alt-5,5'-bithiophene/PS-βCD] (PDOF-BTc) polyrotaxane copolymer, through a Suzuki coupling reaction between the 5,5'-dibromo-2,2'-bithiophene (BT) inclusion complex with persilylated β-cyclodextrin (PS-βCD), and 9,9-dioctylfluorene-2,7-bis(trimethylene borate) (DOF) as the blocking group. The chemical structure and the thermal and morphological properties of the resulting polyrotaxane were investigated by using NMR and FT-IR spectroscopy, TGA, DSC and AFM analysis. The encapsulation of BT inside the PS-βCD cavity results in improvements in the solubility, as well as in different surface morphology and thermal properties of the PDOF-BTc rotaxane copolymer compared to its noncomplexed PDOF-BT homologue. In contrast, the number-average molecular weight (Mn) of PDOF-BTc rotaxane copolymer indicated lower values suggesting that the condensation reaction is subjected to steric effects of the bulkier silylated groups, affecting the ability of the diborate groups from the DOF molecule to partially penetrate the PS-βCD cavity.
Keywords: alternating fluorene-bithiophene copolymer; cyclodextrins; interlocked molecules; macrocycles; persilylated β-cyclodextrin; polyrotaxanes

(untitled) - Chochos, C. L.; Choulis, S. A. (Prog. Polym. Sci., 2011)

(untitled) - Fang, Y. K.; Liu, C. L.; Li, C.; Lin, C.-J.; Mezzenga, R.; Chen, W.-C. (Adv. Funct. Mater., 2010)

(untitled) - Thompson, B. C.; Fréchet, J. M. J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Günes, S.; Neugebauer, H.; Sariciftci, N. S. (Chem. Rev., 2007)

(untitled) - Farcas, A.; Gosh, I.; Jarroux, N.; Guégan, P.; Harabagiu, V.; Nau, W. M. (Chem. Phys. Lett., 2008)

(untitled) - Beinhoff, M.; Appapillai, A. T.; Underwood, L. D.; Frommer, J.; Carter, K. R. (Langmuir, 2006)

(untitled) - Grisorio, R.; Mastrorilli, P.; Nobile, C. F.; Romanazzi, G.; Suranna, G. P.; Acierno, D.; Amendola, E. (Macromol. Chem. Phys., 2005)

(untitled) - Scherf, U.; List, E. J. W. (Adv. Mater., 2002)

(untitled) - Kim, J. H.; Lee, H. (Chem. Mater., 2002)

(untitled) - Bernius, M. T.; Inbasekaran, M.; O'Brien, J.; Wu, W. (Adv. Mater., 2000)

(untitled) - Farcas, A.; Stoica, I.; Stefanache, A.; Peptu, C.; Farcas, F.; Marangoci, N.; Sacarescu, L.; Harabagiu, V.; Guégan, P. (Chem. Phys. Lett., 2011)

(untitled) - Farcas, A.; Hitruc, E. G. (Dig. J. Nanomater. Bios., 2011)
http://www.chalcogen.infim.ro/1649_Farcas.pdf

(untitled) - Zhao, D.; Tang, W.; Ke, L.; Tan, S. T.; Sun, X. W. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Tang, W. H.; Chellappan, V.; Liu, M. H.; Chen, Z. K.; Ke, L. (ACS Appl. Mater. Interfaces, 2009)

(untitled) - Pal, B.; Yen, W.-C.; Yang, J.-S.; Su, W.-F. (Macromolecules, 2007)

(untitled) - Blouin, N.; Leclerc, M.; Vercelli, B.; Zecchin, S.; Zotti, G. (Macromol. Chem. Phys., 2006)

(untitled) - Surin, M.; Sonar, P.; Grimsdale, A. C.; Müllen, K.; Lazzaroni, R.; Leclère, P. (Adv. Funct. Mater., 2005)

(untitled) - Liu, B.; Yu, W. L.; Lai, Y. H.; Huang, W. (Macromolecules, 2000)

(untitled) - Huang, F.; Gibson, H. W. (Prog. Polym. Sci., 2005)

(untitled) - Wenz, G.; Han, B.-H.; Müller, A. (Chem. Rev., 2006)

(untitled) - Frampton, M. J.; Anderson, H. L. (Angew. Chem., Int. Ed., 2007)

(untitled) - Harada, A.; Hashidzume, A.; Yamaguchi, H.; Takashima, Y. (Chem. Rev., 2009)

(untitled) - Farcas, A.; Ghosh, I.; Nau, W. M. (Chem. Phys. Lett., 2012)

(untitled) - Farcas, A.; Fifere, A.; Stoica, I.; Farcas, F.; Resmerita, A.-M. (Chem. Phys. Lett., 2011)

(untitled) - Frampton, M. J.; Sforazzini, G.; Brovelli, S.; Latini, G.; Townsend, E.; Williams, C. C.; Charas, A.; Zalewski, L.; Kaka, N. S.; Sirish, M.; Parrott, L. J.; Wilson, J. S.; et al. (Adv. Funct. Mater., 2008)

(untitled) - Farcas, A.; Jarroux, N.; Guegan, P.; Fifere, A.; Pinteala, M.; Harabagiu, V. (J. Appl. Polym. Sci., 2008)

(untitled) - Farcas, A.; Jarroux, N.; Harabagiu, V.; Guégan, P. (Eur. Polym. J., 2009)

(untitled) - Farcas, A.; Jarroux, N.; Ghosh, I.; Guégan, P.; Nau, W. M.; Harabagiu, V. (Macromol. Chem. Phys., 2009)

(untitled) - Zalewski, L.; Wykes, M.; Brovelli, S.; Bonini, M.; Breiner, T.; Kastler, M.; Dotz, F.; Beljonne, D.; Anderson, H. L.; Cacialli, F.; Samorì, P. (Chem.–Eur. J., 2010)

(untitled) - Broveli, S.; Cacialli, F. (Small, 2010)

(untitled) - Zalewski, L.; Broveli, S.; Bonini, M.; Mativetsky, J. M.; Wykes, M.; Orgiu, E.; Breiner, T.; Kastler, M.; Dötz, F.; Meinardi, F.; Anderson, H. L.; Beljonne, D.; et al. (Adv. Funct. Mater., 2011)

(untitled) - Gibson, H. W.; Farcas, A.; Jones, J. W.; Ge, Z.; Huang, F.; Vergne, M.; Hercules, D. M. (J. Polym. Sci., Part A: Polym. Chem., 2009)

(untitled) - Farcas, A.; Jarroux, N.; Guegan, P.; Harabagiu, V.; Melnig, V. (J. Optoelectron. Adv. Mater., 2007)
http://joam.inoe.ro/download.php?idu=1050

(untitled) - Farcas, A.; Ghosh, I.; Grigoras, V. C.; Stoica, I.; Peptu, C.; Nau, W. M. (Macromol. Chem. Phys., 2011)

(untitled) - Ego, C.; Marsitzky, D.; Becker, S.; Zhang, J.; Grimsdale, A. C.; Müllen, K.; MacKenzie, J. D.; Silva, C.; Friend, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Harabagiu, V.; Simionescu, B. C.; Pinteala, M.; Merrienne, C.; Mahuteau, J.; Guègan, P.; Cheradame, H. (Carbohydr. Polym., 2004)